Analysis on Financing Difficulties for SMEs due to Asymmetric Information - Huang, Cheng; When, Ya; Liu, Zhifei (Global Disclosure of Economics and Business, 2014)
Financing is the bottleneck that restricting the development of China’s small and medium enterprises. The root cause of financing difficulty for SMEs is the serious information asymmetry that exists between financial institutions, which lead to adverse selection and moral hazard. In this paper, financing theories of SMEs information dissymmetry and credit rationing theories are used to analyze the financing difficulties for SMEs and financing strategies to crack financing difficulty are proposed. JEL Classification Code: D82, G32